Social Media and Popularity of Prospective Candidates in the 2019 General Election - Ahmad Fadillah Akbar Rizki; Asep Nurjaman (ARISTO, 2023)
Technology has helped make it easier for people to connect without meeting in person. Social media makes it easier for humans to interact without the need to meet in person. Information that is spread via social media can also apply quickly. This study aims to determine prospective candidates' popularity through social media as a campaign stage for the 2019 General Election. The research method used is descriptive, with a qualitative approach. This study's data sources are primary and secondary. Data collection techniques used are observation, documentation, and literature study. The data analysis technique used is a qualitative descriptive analysis model. The research findings show that social media helps prospective candidates use it as a campaign tool. In addition, social media, as prospective candidates, use a platform to increase their popularity by sharing activity posts featuring promotions or career paths from prospective candidates through their social media. This influence has a good impact on society. Young people, in particular, seem to be drawn to politics via social media.